Quantifying mark-to-market risk in Jamaica’s banking sector - Clarke, Kishan; Stennett, Robert (Universitas Islam Indonesia, 2025)
Purpose — This study evaluates how well parametric Value-at-Risk (VaR) and Conditional Value-at-Risk (CVaR) models measure market risk from Jamaican banks’ sovereign bond exposures.Method — We calibrate VaR and CVaR models using banks’ aggregate portfolio holdings across the entire financial system.Findings — The parametric VaR model performs reliably, passing standard statistical tests for consistency, independence, and reliability.Implications — The results suggest that these standard risk measures effectively capture Jamaican banks’ market risk exposure to foreign currency-denominated sovereign bonds, which could serve as a helpful tool for regulators to monitor market risk and financial system stability.Originality — This research applies VaR and CVaR to a novel dataset of Jamaica’s entire financial system, demonstrating how regulators can transition from the currently prescribed methods. The findings indicate that these standard risk measures effectively capture risk charges for market risk assessment, as allowed under Basel II, and align with more modern Basel-style frameworks.